Zollkrieg und Handelsabkommen zwischen den USA und China; Four years of tariff war and two years of Phase-One agreement between the U. S. and China: Has it worked for the U. S.? - Berend Diekmann; Michael Kilpper (Wirtschaftsdienst, 2022)
Vier Jahre nach Beginn des chinesisch-amerikanischen Zollkriegs und zwei Jahre nach der Unterzeichnung des Phase-One-Abkommens ist ein guter Zeitpunkt gekommen, um die Auswirkungen der Außenhandelspolitik auf die US-Wirtschaft zu untersuchen. Auch wenn die Entwicklungen seit 2019 von anderen Faktoren überlagert und sogar dominiert wurden, fällt dieses Fazit aber eindeutig negativ aus, wie der vorliegende Beitrag zeigt. – – Four years after the Sino-American tariff war started and two years after the "Phase-One" deal was signed, it is a good time to take stock of the outcomes for the U. S. economy. The result is nearly unequivocally negative, in particular, China's failure to fulfill its promises to dramatically increase U. S. imports. By the end of 2021, China had barely reached 40 % of its purchase target for goods. In addition, contrary to political affirmations, initial empirical studies show that American importers have borne the brunt of the tariffs' costs. In the short run, apparently American importers had little choice but to continue to rely on Chinese suppliers. Moreover, improvements in the bilateral trade deficit could not be ascribed to a targeted tariff policy. Nor did manufacturers relocate to the U. S. Instead, trade frictions depressed U. S. business investment. If anything, it may be said that the American managed trade strategy vis-à-vis China has diverted US imports to other suppliers, thus contributing to a diversification of supply chains.
Keywords: F13; F14; Q17; 330; Außenwirtschaftspolitik; Zollpolitik; China; USA